The extent to which nation states have attempted to govern and are continually attempting to govern the internet until today with specific reference to the United States of America, Malaysia and Iraq - Daud, Mahyuddin (Malayan Law Journal, 2010)
The internet has become a significant need at present days. From the day the internet was introduced until now, there have been efforts from governments all around the world to govern the internet. A working group established after a United Nations initiated World Summit on the Information Society ('WSIS') proposed the following definition of internet governance as part of its June 2005 report: